The U.S. Dollar and the World Economy: A Critical Review - Kalim Siddiqui (Athens Journal of Business & Economics, 2020)
The relative decline of the U.S. as a global economic power is clear, and can be seen in the statistics. However, the U.S. decline is nevertheless a slow one, and carries all sorts of unprecedented dangers for the world. The U.S. is definitely in a less powerful position than previously with respect to production, but it is still successfully siphoning off much of the economic surplus (or surplus value) created in the developing countries via the operations of its multinational corporations and its hegemony over the global financial architecture. With respect to U.S. financial dominance, the key issue becomes the continuation of the dollar as the hegemonic currency, which is currently threatened by the rise of China. This paper intends to critically analyse the performance of the U.S. economy and also the role played by the U.S .dollar in the international payment and in reserve currency. The study will also examine the expansion of Chinese economy and importance of the gradual development of a multicurrency system with the intention of reducing the growing balance of payments deficit putting pressure on a single reserve currency. This study has followed doctrinaire methodology, which includes analytical, descriptive and comparative methods. This article concludes that the U.S. economy is currently suffering from a serious trade deficit and the position of the U.S. dollar is under genuine threat from the renminbi, the renminbi will not be able to replace the U.S. dollar as the global currency for at least the next decade